2017
DOI: 10.2147/ott.s99282
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pretreatment albumin–globulin ratio in predicting long-term mortality in gastric cancer patients who underwent D2 resection

Abstract: BackgroundSeveral studies have highlighted the prognostic value of the albumin–globulin ratio (AGR) in various kinds of cancers. Our study was designed to assess whether AGR is associated with the prognosis of gastric cancer patients.Patients and methodsA total of 507 gastric cancer patients between 2005 and 2012 were included. The AGR was defined as the ratio of serum albumin to nonalbumin and calculated by the equation: albumin/(total protein − albumin). Furthermore, AGR was divided into two groups (low and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 32 publications
2
22
3
Order By: Relevance
“…However, its role in cancer suppression has not yet been well investigated. In Liu et al’s study, no relationship was found between baseline GLOB level and OS in patients with gastric cancer. In this study, K‐M survival analysis in both its test and validation sets showed little association between baseline GLOB and OS.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…However, its role in cancer suppression has not yet been well investigated. In Liu et al’s study, no relationship was found between baseline GLOB level and OS in patients with gastric cancer. In this study, K‐M survival analysis in both its test and validation sets showed little association between baseline GLOB and OS.…”
Section: Discussioncontrasting
confidence: 66%
“…In addition to ALB and GLOB, the level of AGR was also analyzed. It has been reported that a low level of AGR has the potential to be a predictor for poor prognosis for breast cancer, gastric cancer, colorectal cancer, and lung cancer . However, in this study, the median of AGR was 1.5 (ranging from 0.6 to 2.3).…”
Section: Discussioncontrasting
confidence: 66%
“…To overcome this defect, numerous recent studies have tried to investigate the prognostic significance of the albumin/globulin ratio (AGR) in cancer patients, which combines two factors and thus might reduce the influence of confounding factors. For instance, a body of studies reported that a low pretreatment AGR is closely associated with worse prognosis in patients with digestive system cancers, such as gastric cancer[ 9 , 10 ], colorectal cancer [ 11 – 15 ], pancreatic cancer[ 16 ], hepatocellular carcinoma[ 17 ] and so on. However, most studies published to date use a small sample size, which might affect the reliability of their conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 40% of all GC cases occur in China and these are often diagnosed in the advanced stages [ 3 , 4 ]. The 5 year survival rate was 28% in 2014 [ 5 ]. Many factors result in the occurrence of GC, including genetic and epigenetic alterations.…”
Section: Introductionmentioning
confidence: 99%